2009
DOI: 10.19173/irrodl.v10i4.725
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluative Study of a Distance Teacher Education Program in a University in Ghana

Abstract: The study used an adaptation of Provus' discrepancy evaluation model to evaluate a distance teacher education program in the University of Cape Coast, the premier teacher education institution in Ghana. The study involved comparing performance data of the program as perceived by students and faculty/administrators to standards prepared from the program's design. Performance data was obtained by administering two survey instruments to a random sample of students and faculty/administrators. Discrepancies between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Because the value of the teaching practice experience in the cooperating schools seems to depend on the quality of the cooperating teachers, organizers of the blended English language teacher education program should pay more attention to the selection of cooperating teachers. Along the same lines, Sampong (2007) claims that distance pre-service teacher education is executed efficiently when the practicum component is planned properly and is well supervised by qualified master teachers. Therefore, cooperating teachers should be selected based on specific criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Because the value of the teaching practice experience in the cooperating schools seems to depend on the quality of the cooperating teachers, organizers of the blended English language teacher education program should pay more attention to the selection of cooperating teachers. Along the same lines, Sampong (2007) claims that distance pre-service teacher education is executed efficiently when the practicum component is planned properly and is well supervised by qualified master teachers. Therefore, cooperating teachers should be selected based on specific criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Coates, 2009;Mishra et al, 2009;Sampong, 2009;Sampson, 2003;Taylor-Powell & Renner, 2000). The questions in the second survey were also based on the learning outcomes of the programme, as well as the principles that guide the programme (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 provides the layout of the modules. (Perraton, 2007), Turkey (Gültekin, 2009), India (Mishra, Vijayshri, & Garg, 2009), the United Kingdom (Sampong, 2009;Wilson, 2008), and Australia (Sampong, 2009).…”
mentioning
confidence: 99%
“…The critical issue of GT-led policy implementation was not addressed, a gap that this research seeks to bridge. In the specific case of distance education programs in Ghana, evaluative studies have been carried out involving the leading two programs [53], a multi-case study of four public universityoperated programs [5], and a teacher education program [13]. In essence, findings of these studies suggested that implementation of distance education strategies was severely hampered.…”
Section: Strategy Implementation Efforts In Ghanamentioning
confidence: 99%
“…Although indigenous strategy implementers have often attributed such failures to inadequate allocation of resources [6], similar projects managed by non-Ghanaians, with similar funding arrangements and terms of reference, are often devoid of these shortcomings [7]. This rhetoric suggests that the Ghanaian worker probably executes strategies other than those specified in organizational roadmapsa faux pas that is often interestingly justified as a Ghanaian Thing (GT) [8], or unproductive but celebrated workplace practices, including "organizational inertia" [9], dumsorization [10], deliberate resistance to change [11], ineffective communication [12], lack of evaluation and control mechanisms [13], and corruption [14. This paper interrogates these workplace practices in order not only to provide insight into the ubiquitous incidence of implementation setbacks in Ghana's public sector organizations, but also help create pathways for overcoming the menace. Specifically, the study sought to understand the operations of GT networks, using the nation's Distance Education Program (DEP) as a case study.…”
Section: Introductionmentioning
confidence: 99%